Advances in genetic diagnosis and therapy of hereditary heart disease: a bibliometric review from 2004 to 2024 - Ma, Huixi; Wang, Yun; Jia, Yang; Xie, Linjun; Liu, Lini; Zhang, Dingyi; Ma, Xinyue; Guo, Yingkun; Xu, Rong (Frontiers in Medicine, 2025)
Hereditary heart disease (HHD) is a series of cardiac disorders associated with monogenic or polygenic abnormalities and is one of the leading causes of sudden death, particularly in young adults. The updated European Cardiology guideline for cardiomyopathies provides the first comprehensive summary of genotyping, imaging, and therapy recommendations for inherited cardiomyopathies, but still lacks a comprehensive discussion of research advances and future trends in genetic diagnosis and therapy of HHD. Our research aims to fill this gap. Bibliometric analysis software (CiteSpace 6.3.R1, VOSviewer 1.6.18, and Scimago Graphica) was used to analyze the general information, trends, and emerging foci of HHD in the past 20 years, including author, country, institution, keyword, and so on. There were 5,757 publications were screened and aggregated in the database, including 1876 reviews and 3,881 articles. Hypertrophic cardiomyopathy (HCM), arrhythmogenic cardiomyopathy (ACM), Brugada syndrome (BrS), myocardial amyloidosis, and Fabry disease (FD) were the main types of HHD that were explored in greater depth. Moreover, new diagnostic methods, clinical cohorts, and genetically targeted therapies for HHD patients are key research hotspots. The relationship between the pathogenicity of genes and prognosis will become increasingly important for therapy.